2021
DOI: 10.1088/1742-6596/1755/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Graphical password based mouse behavior technique

Abstract: This paper proposes a new password generation technique on the basis of mouse motion and a special case location recognized by the number of clicks to protect sensitive data for different companies. Two, three special locations click points for the users has been proposed to increase password complexity. Unlike other currently available random password generators, the path and number of clicks will be added by admin, and authorized users have to be training on it. This method aims to increase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Start by connecting it to a USB port, an AC adapter, or a battery. The Arduino Uno R3 was used in this study [35]- [38].…”
Section: Arduino Microcontroller Boardmentioning
confidence: 99%
“…Start by connecting it to a USB port, an AC adapter, or a battery. The Arduino Uno R3 was used in this study [35]- [38].…”
Section: Arduino Microcontroller Boardmentioning
confidence: 99%
“…Smart phones use Bluetooth technology developed by Ericsson in 1994, which demonstrates its usefulness. Digital technology is now used both at home and at work, leading to a shift away from wired digital devices [13]- [16]. Up to seven Bluetooth modules can be connected to a host device simultaneously through a single link [16]- [18].…”
Section: Introductionmentioning
confidence: 99%
“…Digital technology is now used both at home and at work, leading to a shift away from wired digital devices [13]- [16]. Up to seven Bluetooth modules can be connected to a host device simultaneously through a single link [16]- [18]. Combining twelve physical components, programming languages, and software creates an even better product.…”
Section: Introductionmentioning
confidence: 99%
“…Important aspects of authentication systems like password resets and replacements are also discussed. Abdalkareem et al, (2021) [14], To protect confidential information, this paper suggests a novel method of password generation based on mouse movement and a special case location recognized by the number of clicks. It has been suggested that users click in two or three distinct places to require more complex passwords.…”
mentioning
confidence: 99%